Resepsi Siswa dan Siswi terhadap Hadis tentang Shalat Dhuha di MTs Raudlatul Uluum Aek Nabara - Nur Annisa; Sulaiman Muhammad Amir (CV Global Research Publication, 2026)
This study aims to analyze students’ reception of the hadiths concerning Duha prayer at MTs Raudlatul Uluum Aek Nabara from the perspective of Living Hadith. The research employed a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that students’ reception of the hadiths on Duha prayer is manifested in two primary dimensions: exegetical reception and functional reception. Exegetical reception is reflected in students’ understanding that Duha prayer is a Prophetic tradition (sunnah), a means of drawing closer to Allah, and a practice that brings blessings. Functional reception is evident in the implementation of congregational Duha prayer, which has become a religious culture within the madrasa and is practiced by approximately 95% of the students. The practice provides various benefits perceived by the students, including increased learning motivation, discipline, psychological well-being, self-confidence, moral development, and harmonious social relationships. These findings indicate that the hadiths concerning Duha prayer are not merely understood as normative religious teachings but are also actualized in daily life, contributing to the development of students’ religious character.